Eventos de letramento na disciplina de artes de uma escola de educação profissional: formação para a cidadania planetária - Matias, Ana Paula (2019)
This research presents reading and the arts as activities that integrate the areas of knowledge and the construction of new knowledge that circulate in the school environment, especially in the construction of a curriculum that seeks, in addition to the cognitive dimension, an affective, motor and ethical perspective. It is understood, therefore, that the teaching of Arts is intertwined with the reading practice in the school context, since Art glimpses several languages, oral and written, responsible for developing the opinion and critical reasoning of students, dialoguing with the social, historical and cultural contexts in which the individual is inserted. It aims to analyze literacy events in the discipline of Arts that contribute to the formation of planetary citizenship. It was held with students from the 2nd year of high school of a professional school, in the city of Caucaia, Ceará. It is supported by theoretical studies on Practice and Teaching, such as those of Freire (2011); of assimilation of meaning of Koch (1998); literacy, of Colello (2010), Mendonça (2007) and Soares (2003), and the relations between the discursive/textual genders and the sociocultural context of the learner building interdisciplinary relationships, according to Japiassu (1992); Libâneo (1998), Moraes (2005) and Fazenda (2008). It approaches the historical path and the construction of citizenship in our society presenting the meaning and conceptual implication of the term citizenship. It defines the conception of planetary citizen from the perspective of Gadotti (1999), (2000); Morin (2001, 2011) and Moraes (2018). These initial concepts fell into a much broader category called curriculum. The profile and curriculum of vocational education schools in the State of Ceará were described from data collected in the SEDUC portal and in the research locus. It uses as methodological approach the participant observation, the focus group and semi-structured interviews, as qualitative research. It presents as results that the literacy events related to the various artistic languages - visual, theatrical, corporal and musical - produce a more effective learning for the construction of citizenship, because they have the perspective of addressing in the curriculum the various themes, as the essential issues of human existence and to dialogue with the rights and duties for a democratic society, contributing to overcoming prejudices and individualistic postures. With this, it is concluded that the events of literacy in the discipline of Arts, in the locus in question, are preparing young people to exercise their project of life at the end of high school.